Monocyte/HDL-cholesterol ratio as an early prognostic marker of pregnancy complications development - Vulić, Jovana; Radojković, Jelena; Vekić, Jelena; Stefanović, Aleksandra; Ardalić, Daniela; Miković, Željko; Gojković, Tamara; Munjas, Jelena; Zeljkovic, Aleksandra (Archives of Pharmacy, 2025)
Pregnancy complications increase the long-term cardiovascular risk for both the mother and the child. Inflammation is a common mechanism underlying the development of pregnancy complications and atherosclerosis. This study aims to investigate whether the monocyte/HDL cholesterol ratio can serve as a predictive marker for the risk of pregnancy complications. A total of 84 pregnant women participated in this study, 41 of whom had a normal pregnancy course, while 43 experienced complications. Lipid status parameters were measured using enzymatic methods and total blood count was measured using a hematology analyzer. In the first trimester of pregnancies with complications we observed significantly higher levels of total cholesterol (P < 0.01), low-density lipoprotein cholesterol (LDL-C) (P < 0.01) and triglycerides (P < 0.001) compared to pregnancies without complications, whereas no differences were observed in high-density lipoprotein cholesterol (HDL-C). Pregnant women with complications had a significantly higher proportion of monocytes throughout the entire pregnancy, and lower concentrations of HDL-C in the second trimester (P < 0.05). The risk of developing complications in pregnancy was 11 times higher if the monocyte/HDL-C ratio was elevated in the first trimester (OR: 11.42; 95%CI: 4.05–32.19; P < 0.001). Our results indicate that monocyte/HDL-C ratio could be used as a simple and cost-effective early prognostic biomarker of pregnancy complications.
Keywords: pregnancy; complications; monocyte/HDL-C ratio